1999
DOI: 10.2144/99264rr03
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble, Meso-Substituted Cationic Porphyrins—a Family of Compounds for Cellular Delivery of Oligonucleotides

Abstract: The delivery of oligonucleotides to appropriate intracellular compartments is crucial to their development as tools in gene function studies and as therapeutics. Here, we report the characterization of meso-substituted cationic porphyrins as a large class of water-soluble reagents for oligonucleotide delivery. These porphyrins form non-covalent complexes with single-stranded oligonucleotides and deliver these molecules into the nuclei of cell lines in culture. The porphyrins protect oligonucleotides from nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Generally in the form of their metal complexes, they function, for example, as prosthetic groups in oxidation catalysts [2], reversible oxygen transporters [3], catalysts in hydrocarbon biosynthesis [4], are believed to be involved in the cellular delivery of oligonucleotides [5] and oligoribonucleotides [6], or they function as antennas and reactive centers in light harvesting systems [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Generally in the form of their metal complexes, they function, for example, as prosthetic groups in oxidation catalysts [2], reversible oxygen transporters [3], catalysts in hydrocarbon biosynthesis [4], are believed to be involved in the cellular delivery of oligonucleotides [5] and oligoribonucleotides [6], or they function as antennas and reactive centers in light harvesting systems [7].…”
mentioning
confidence: 99%
“…As judged by its optical properties, its coordination properties are expected to be much more similar to those of diolchlorin complex [4]Co than those of porpholactone [2]Co. We have also included two pyrrole-modified porphyrins, morpholinochlorin [3]Co, and indaphyrin [5]Co in our study [43,44,45]. While free base morpholinochlorin 3 incorporating a sixmembered ring in the macrocycle structure is nearly as planar as a porphyrin/chlorin and it possesses chlorin-like optical properties [43], its coordination properties may be significantly different than those of porphyrins or chlorins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical procedures such as the use of cationic lipid reagents (Zelphati and Szoka, 1996), streptolysin O-mediated plasma membrane permeabilisation (Spiller and Tidd, 1995), an amphiphilic anionic peptide (Pichon et al, 1997) or cationic porphyrin derivative (Flynn et al, 1999) also result in the ONs being introduced directly into the cytosol, from where they migrate within minutes to the nucleus. Zelphati and Szoka (1996) demonstrated that there was no effect by Brefeldin A on movement of PS-ONs from the cytoplasm to the nucleus.…”
Section: The Importance Of Nuclear Entry For Oligonucleotidesmentioning
confidence: 99%
“…They thus represent promising class of medical drugs for healing various viral, malignant and genetic diseases [1,2]. Since polyanionic and hydrophilic oligonucleotides cannot diffuse easily through membrane into the cells, various penetration enhancers have been realized and studied as delivery agents, including water-soluble cationic porphyrins [3][4][5]. Due to Coulombic compensation of the negative charge, hydrophilicity of the oligonucleotides can be considerably reduced without preventing them from stronger and more specific interaction with targets inside the cells.…”
Section: Introductionmentioning
confidence: 99%